Interface‐Strengthened Polymer Nanocomposites with Reduced Dielectric Relaxation Exhibit High Energy Density at Elevated Temperatures Utilizing a Facile Dual Crosslinked Network. Issue 22 (6th May 2020) - Liu, Jie; Shen, Zhonghui; Xu, Wenhan; Zhang, Yu; Qian, Xiaoshi; Jiang, Zhenhua; Zhang, Yunhe
Abstract: High‐temperature ceramic/polymer nanocomposites with large energy density as the reinforcement exhibit great potential for energy storage applications in modern electronic and electrical power systems. Yet, a general drawback is that the increased dielectric constant is usually achieved at the cost of decreased breakdown strength, thus leading to moderate improvement of energy density and even displaying a marked deterioration under high temperatures and high electric fields. Herein, a new strategy is reported to simultaneously improve breakdown strength and discharged energy density by a step‐by‐step, controllable dual crosslinking process, which constructs a strengthened interface as well as reduces molecular chains relaxation under elevated temperatures. Great breakdown strength and discharged energy density is achieved in the dual crosslinked network BT‐BCB@DPAES nanocomposites at elevated temperatures when compared to noninterfacial‐strengthened, BT/DPAES composites, i.e., an enhanced breakdown strength and a discharged energy density of 442 MV m −1 and 3.1 J cm −3, increasing by 66% and 162%, and a stable cyclic performance over 10 000 cycles is demonstrated at 150 °C. Moreover, the enhancement through the synergy of two crosslinked networks is rationalized via a comprehensive phase‐field model for the composites. This work offers a strategy to enhance the electric storage performances of composites at high temperatures. Abstract : Dual crosslinked network achieved by a well‐controlled, step‐by‐step crosslinking strategy, leading to an ultrastable dielectric polymer nanocomposite, exhibits a significantly enhanced high‐temperature dielectric stability, owing to the strengthened interfaces and reduced molecular chains relaxation. More notably, the high‐temperature energy storage properties under the high fields and high‐temperature have significantly enhanced.